Hemolysis of human blood cells induced by gasohol in vitro model: the preliminary study - Tunsaringkarn, Tanasorn; Soogaroon, Suphan; Moungkote, Tusrin; Palasuwan, Attakorn (International Journal of Research in Medical Sciences, 2017)
Background:Ethanol has been shown to inhibit spontaneous cell-mediated cytotoxicity and antibody-dependent cell-mediated cytotoxicity in vitro in a dose-dependent manner. A mixture of ethanol in biofuel may show interaction with respect to spontaneous and cell-mediated cytotoxicity. Methods:The cytotoxicity on Human Red Blood Cells (RBCs) and White Blood Cells (WBCs) was studied in vitro model of 4 types of biofuels (gasohol) (octane 91, octane 95, E 20, and E 80) in serial dilutions. The lysis and abnormal morphology of cells were analyzed by colorimetric and microscopic methods. Results:Quantitative hemolysis of RBCs was increased with rising ethanol concentration as well as abnormal morphology of RBCs like spherocyte. Moreover, ethanol might effect to lysis and morphology of WBCs. Conclusion:It is suggested that the gasohol-induced cytotoxicity may be related to concentration of ethanol in gasohol. However, it is possible to future study on mechanism of action leading to cell lysis and kinetic of morphological change in RBCs and WBCs.